Augmented Reality-Based Board Game for Learning English for Junior High School Students - Handy Putra Maslan; Erdhi Widyarto Nugroho; FX Hendra Prasetya (Journal of Business and Technology, 2022)
English is the language used by all countries as the main communication tool. By understanding English, young people can have the opportunity to work abroad and gain more knowledge and better job opportunities. But education in Indonesia and the willingness of young people to learn is still low, young people tend to prefer to play games rather than learn. Therefore, a game made with Augmented Reality technology was combined with a Board Game called the game "ArReadSpeed" in hopes of helping young people especially those still sitting in junior high schools (SMP) to learn while playing. This game can be played by 4 people, so we can give free time children the game "ArReadSpeed". But because currently there is a Corona pandemic, the data search and testing process must be changed by going through online classes. The purpose of this study is about how to formulate games so that it can make young people more easily learn English lessons. The formulation in it determines the gameplay, reward system, and punishment for incorrectly answering questions. After the game was finished, some junior high school children were tested and the results were that performance expectations (usability) and entertainment (pleasure) had a correlation with the variable wanting to continue to use (desire to use again).